A significant association between deltamethrin resistance, Plasmodium falciparum infection and the Vgsc-1014S resistance mutation in Anopheles gambiae highlights the epidemiological importance of resistance markers - Kabula, Bilali (Malar J, 2016)
BACKGROUND: The success of malaria vector control is threatened by widespread pyrethroid insecticide resistance. However, the extent to which insecticide resistance impacts transmission is unclear. The objective of this study was to examine the association between the DDT/pyrethroid knockdown resistance mutation Vgsc-1014S, commonly termed kdr, and infection with Plasmodium falciparum sporozoites in Anopheles gambiae. METHODS: WHO standard methods were used to characterize susceptibility of wild female mosquitoes to 0.05 % deltamethrin. PCR-based molecular diagnostics were used to identify mosquitoes to species and to genotype at the Vgsc-L1014S locus. ELISAs were used to detect the presence of P.falciparum sporozoites and for blood meal identification. RESULTS: Anopheles mosquitoes were resistant to deltamethrin with mortality rates of 77.7 % [95 % CI 74.9–80.3 %]. Of 545 mosquitoes genotyped 96.5 % were A. gambiaes.s. and 3.5 % were Anopheles arabiensis. The Vgsc-1014S mutation was detected in both species. Both species were predominantly anthropophagic. In A. gambiaes.s., Vgsc-L1014S genotype was significantly associated with deltamethrin resistance (χ2 = 11.2; p < 0.001). The P. falciparum sporozoite infection rate was 4.2 %. There was a significant association between the presence of sporozoites and Vgsc-L1014S genotype in A. gambiaes.s. (χ2 = 4.94; p = 0.026). CONCLUSIONS: One marker, Vgsc-1014S, was associated with insecticide resistance and P. falciparum infection in wild-caught mixed aged populations of A. gambiaes.s. thereby showing how resistance may directly impact transmission.